SISTEM PAKAR PENDETEKSI KERUSAKAN KAMERA DSLR MENGGUNAKAN METODE CF (CERTAINTY FACTOR) - Juewanto -; Muhammad Sholeh; Erfanti Fatkhiyah (Jurnal SCRIPT, 2018)
In this digital era, all people have possibility to do anything including to document the moments with the digital camera based on Digital Single Lens Reflex, but sometimes inappropriate procedure of the usage could cause the damage for the camera, as a commoner absolutely will be confused with the problem that occurs when the damage happens and they will decide to bring a new one or sell it, whereas the damage camera still can be fixed by yourself or an expert technician. To solve the existing problem, then created an expert System based on the web to diagnose the damages in the Digital Single Lens Reflex camera, with many methods to produce an application that will be made start from the interview with an expert technician to determine all sorts of parameters that will be used until the Certainty Factor as a logarithm calculation to plan and implement the system. The result of this expert System application to diagnose the damages in Digital Single Lens Reflex camera including what kind of damage that happens and the alternative solution. After making this application could help people to be sensitive about the condition of Digital Single Lens Reflex camera, in the care side, until the repair if there is a simple damage.